An ultrahigh-contrast and broadband on-chip refractive index sensor based on a surface-plasmon-polariton interferometer - Wang, Yujia; Chen, Jianjun; Sun, Chengwei; Rong, Kexiu; Li, Hongyun; Qihuang Gong (ANALYST, 2015)
Using a double-slit structure fabricated on a gold film or a subwavelength (300 nm) plasmonic waveguide, high-contrast and broadband plasmonic sensors based on the interference of surface plasmon polaritons (SPPs) are experimentally demonstrated on chips. By adjusting the focused spot position of the p-polarized incident light on the double-slit structure to compensate for the propagation loss of the SPPs, the interfering SPPs from the two slits have nearly equal intensities. As a result, nearly completely destructive interference can be experimentally achieved in a broad bandwidth (>200 nm), revealing the robust design and fabrication of the double-slit structure. More importantly, a high sensing figure of merit (FOM*) of >1 x 10(4) RIU-1 (refractive index unit), which is much greater than the previous experimental results, is obtained at the destructive wavelength because of a high contrast ratio (C = 0.96). The high-contrast and broadband on-chip sensor fabricated on the subwavelength plasmonic waveguide may find important applications in the real-time sensing of particles and molecules.